2003
DOI: 10.1007/s00586-002-0520-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a bipedicular spinal fixation device: three different strength tests

Abstract: IntroductionDuring the last 40 years, surgical correction techniques applied to spinal deformity have progressed radically. Harrington [8], Luque [14], and then Cotrel and Dubousset [6] added successive contributions to these advances using different approaches. Harrington [8] chose a simple distraction, correcting deformation essentially in the frontal plane. Luque [14] obtained this same distraction by translating the spine toward the rods, which were fixed by laminar wires. Cotrel and Dubousset [6] introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It has been assumed that failure strength is determined not only by BMD and implant type, but also by pedicle strength, cortical thickness, and pedicle dimensions. 1 In Group B (normal bone quality) failure of the hook claws occurred with significantly less force (p = 0.02) compared with the other systems. These findings are consistent with the observations of Hackenberg et al 16 who noted that pedicle screws provided superior stability compared with hooks in thoracic spines with BMD > 100 mg/ml.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been assumed that failure strength is determined not only by BMD and implant type, but also by pedicle strength, cortical thickness, and pedicle dimensions. 1 In Group B (normal bone quality) failure of the hook claws occurred with significantly less force (p = 0.02) compared with the other systems. These findings are consistent with the observations of Hackenberg et al 16 who noted that pedicle screws provided superior stability compared with hooks in thoracic spines with BMD > 100 mg/ml.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, there is limited data on thoracic instrumentation comparing various fixation systems and the effect of their performance related to BMD on fixation strength. [1][2][3][4]6,7,23 One of the most accepted methods to evaluate the strength of the implant-bone interface has been the pullout test because it is simple, reproducible, and allows for direct comparisons. [2][3][4]6,12,13,16,19,27,32,36,37,40,43 The aim of this study was to investigate the effect of BMD on the axial pullout strength of 4 widely used posterior thoracic fixation systems: pedicle screws, laminar hooks, sublaminar wires, and pedicle screws augmented with sublaminar wires.…”
mentioning
confidence: 99%
“…The description of the geometrical features of the entire experimental set-up was originally based on unpublished measurements taken on two-level constructs cited in a previous experimental work. 11 Even if many authors 2053 reported a great amount of data describing the morphometric/anatomical features of the VBs (Table 1), only Chaynes et al 35 investigated the geometrical relationship describing a complete functional spine unit (FSU) in relation to pedicle screw fixation. These parameters determine the final geometrical configuration of a spinal fixator and it would be very useful to determine the features of the experimental set-up closer to the clinical use, in order to build up a preclinical experimental set-up really representative of the clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…Most experiments are done with pull-out test to investigate the fixation strength of single pedicle screws [4,[11][12][13][14][15][16][17][18][19][20][21] or other posterior fixation systems [16,20,22]. Sometimes screws are also tested with so-called toggling tests where cyclic bending moments are used [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%